(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Competence ability, and even company survival in today’s dynamic and relatively unpredictable global business environment, are both becoming increasingly dependent on knowledge, skills and employee competence, as well as their work motivation. Thus, in these times of harsh competition, companies seek ways through which to increase employee readiness to fulfill company goals. Individuals are pushed for action by different motivators, awards and stimulations, all of which mirror their wishes. The task of every manager is to use motivators in order to stimulate employee performance, or drive them to complete their duties. The aim of this paper is to identify those factors that have a motivating effect on the employees working in companies across Bosnia and Herzegovina. The research included workers from different organizations in order to establish a relationship between organizational characteristics and the motivating effects of various factors. The methodological framework of this work has its basis in Herzberg’s Two Factor Theory of Motivation. A special challenge for the empirical research, conducted through surveys distributed across companies in Bosnia and Herzegovina, was the identification of motivators which stimulate employee action. The results of this research could help managers in finding answers to different strategies of employee motivation, as well as in increasing their own capability in motivating workers and employing inventive motivators.